Comparative study of evolution process and structure of systematized nomenclature of medicine in America , England and Australia countries - R Safdari; M Ghazisaeedi; E Partovipoor; H Farajzadeh saray (Tehran University of Medical Sciences, 2008)
Background and Aim: Systematized Nomenclature of Medicine systems are the important supportive for electronic health record in registration and retrieval of data. Systematized Nomenclature of Medicine - Clinical Terms (SNOMED CT) is the most comprehensive language and then the consistency of exchanged data across health care providers and finally the high effectiveness of health care. Materials and Methods : This research is a descriptive - comparative study and has been done in certain time section. Ideally , it have been used the descriptive - comparative method for studying of selective countries. Results : Findings of this study show that American and England countries have accepted the SNOMED CT with application in all clinical activities and Australia country is evaluating this system and is using older versions of SNOMED only in pathologic applications now. Study shows that SNOMED CT structure is complex and based of concept (clinical concept) and contains two fundamental parts : 1) content of SNOMED CT core (concepts , descriptions and relations) that are always constant 2) content of out of SNOMED CT core (mappings or relation with systems and local extensions) that according to health and management needs and native terms of country are different. Such a structure executes in different software applications. Conclusion : SNOMED CT structure in America and England countries has been compared and with attention to similarities (content of SNOMED CT core) and differences (content of out of SNOMED CT core : cross mappings and local extensions) , a basic SNOMED CT structure has been provided for Iran. Because of SNOMED CT in Australia is under development, researcher has studied its evolution and execution process in this country and has provided an appropriate structural pattern for Iran.